Usability Testing Pada Aplikasi Mobile E-Ganesha Undiksha Mengunakan Metode System Usability Scale - Kusuma Wardana, Kadek; Erna Supriathi, Ni Kadek; Suarka, I Nyoman; Parahita Nugraha, Gemara Adhiyasa; Oka Gunawan, I Made Agus; Indrawan, Gede (STMIK Sinar Nusantara, 2024)
E-Ganesha is a system built for all academic activities in Ganesha Singaraja University. User satisfaction with the application is a crucial factor in retaining users and the program's existence. The aim of this research is to determine the level of satisfaction of E-Ganesha users using the System Usability Scale (SUS) method. One of the benefits of using the System Usability Scale (SUS) is its simplicity to apply and the method is well-received by responders due to its easily understandable questions. This research used descriptive and survey methods, with 20 respondents from undergraduate and master's program students in Undiksha. By using the System Usability Scale (SUS) method, this research produced its score with an average of 87.5. E-Ganesha application is included in the 'ACCEPTABLE' category on the Grade Scale, indicating that users can accept it. This is indicated by the application's placement in the Acceptability Ranges ‘B', where the term